2018
DOI: 10.1148/radiol.2018180628
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer CT: Prediction of Resectability according to NCCN Criteria

Abstract: To evaluate the diagnostic performance of CT in the determination of pancreatic cancer resectability according to the National Comprehensive Cancer Network (NCCN) criteria to predict R0 resection. Materials and Methods: Structured reports of pancreatic CT clinically prepared by board-certified abdominal radiologists from January 2014 to March 2017 were retrospectively reviewed to assess resectability (resectable, borderline resectable, or unresectable) according to NCCN criteria (version 1.2017) in 616 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 30 publications
(32 reference statements)
2
42
1
3
Order By: Relevance
“…PDAC has been classified into three categories: i) resectable (R), ii) borderline resectable (BR), or iii) unresectable (UR), based on residual tumor status evaluated by contrast-enhanced multidetector-row computed tomography (MDCT). Although a better R0 resection rate can be achieved in patients with R-PDAC compared to patients with BR-or UR-PDAC, the 5year OS remains unsatisfactory (8)(9)(10).…”
mentioning
confidence: 99%
“…PDAC has been classified into three categories: i) resectable (R), ii) borderline resectable (BR), or iii) unresectable (UR), based on residual tumor status evaluated by contrast-enhanced multidetector-row computed tomography (MDCT). Although a better R0 resection rate can be achieved in patients with R-PDAC compared to patients with BR-or UR-PDAC, the 5year OS remains unsatisfactory (8)(9)(10).…”
mentioning
confidence: 99%
“…In 2016, an international consensus was adopted in Japan to standardize the classification of pancreatic cancer resectability [6,7]. Today, pancreatic cancer is considered resectable when tumor mass does not affect the arterial blood vessels of the upper mesenteric artery (AMS), the coeliac trunk (TC) and the common hepatic artery (ACH), the blood vessels of the upper mesenteric vein (VMS), and/or vena portalis (VP) or narrows them by less than 180° [8].…”
Section: Ct Resectability Criteria Of Pancreatic Carcinomamentioning
confidence: 99%
“…Several imaging features for evaluating surgical PV-SMV invasion have been introduced, including encasement (>180°) of the tumor-vein relationship (13), deformation, narrowed or stenotic morphology of PV-SMV (14), and the teardrop sign (15). Unfortunately, such above qualitative imaging findings do not accurately classify vascular involvement, especially in peripancreatic venous involvement (16)(17)(18). Also, a recent study showed that agreements in the interpretation of tumor-vascular relationships were low among different observers (19).…”
Section: Introductionmentioning
confidence: 99%